EPIDEMIOLOGICAL PECULIARITIES AND LAMBLIASIS RISK FACTORS AMONG CHILDREN WITH CHRONIC DIGESTIVE DISEASES - R.A. Akhmetova; R.T. Akhmetov; E.O. Moskvicheva; G.T. Tupertseva; T.R. Akhmetov ("Paediatrician" Publishers LLC, 2007)
.